Probiotic yogurt and acidified milk similarly reduce postprandial inflammation and both alter the gut microbiota of healthy, young men. Issue 9 (31st May 2017) - Burton, Kathryn J.; Rosikiewicz, Marta; Pimentel, Grégory; Bütikofer, Ueli; von Ah, Ueli; Voirol, Marie-Jeanne; Croxatto, Antony; Aeby, Sébastien; Drai, Jocelyne; McTernan, Philip G.; Greub, Gilbert; Pralong, François P.; et al.
Abstract: Probiotic yogurt and milk supplemented with probiotics have been investigated for their role in 'low-grade' inflammation but evidence for their efficacy is inconclusive. This study explores the impact of probiotic yogurt on metabolic and inflammatory biomarkers, with a parallel study of gut microbiota dynamics. The randomised cross-over study was conducted in fourteen healthy, young men to test probiotic yogurt compared with milk acidified with 2 %d -(+)-glucono- δ -lactone during a 2-week intervention (400 g/d). Fasting assessments, a high-fat meal test (HFM) and microbiota analyses were used to assess the intervention effects. Baseline assessments for the HFM were carried out after a run-in during which normal milk was provided. No significant differences in the inflammatory response to the HFM were observed after probiotic yogurt compared with acidified milk intake; however, both products were associated with significant reductions in the inflammatory response to the HFM compared with the baseline tests (assessed by IL6, TNF α and chemokine ligand 5) ( P <0·001). These observations were accompanied by significant changes in microbiota taxa, including decreased abundance of Bilophila wadsworthia after acidified milk (log 2-fold-change (FC)=–1·5, P adj =0·05) and probiotic yogurt intake (FC=–1·3, P adj =0·03), increased abundance of Bifidobacterium species after acidified milk intake (FC=1·4, P adj =0·04) and detection of Lactobacillus delbrueckii spp. bulgaricus (FC=7·0, P adj <0·01) and Streptococcus salivarius spp. thermophilus (FC=6·0, P adj <0·01) after probiotic yogurt intake. Probiotic yogurt and acidified milk similarly reduce postprandial inflammation that is associated with a HFM while inducing distinct changes in the gut microbiota of healthy men. These observations could be relevant for dietary treatments that target 'low-grade' inflammation.